2015
DOI: 10.1371/journal.pone.0132380
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Chromosome Painting and NOR Distribution Suggest a Complex Hybrid Origin of Triploid Lepidodactylus lugubris (Gekkonidae)

Abstract: Parthenogenesis, unisexuality and triploidy are interesting but poorly studied phenomena occurring in some reptile species. The mourning gecko (Lepidodactylus lugubris) represents a complex of diploid and triploid parthenogenetic mostly all-female populations (males occur quite rarely) widely distributed in coastal areas of the Indian and Pacific Oceans. Here, we study karyotypes of a male and two female L. lugubris (LLU) triploid individuals (3n = 66) using comparative painting with Gekko japonicus, Hemidacty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…The number and chromosomal distribution of NOR sites have been traditionally regarded as of taxonomical relevance and used many times for taxonomical inferences [see Odierna et al, 1987;Olmo et al, 1990 and references therein;Caputo et al, 2009;Trifonov et al, 2015]. Silver staining revealed a single NOR site, located on a medium-small [MS sensu Olmo et al, 1990] pair of chromosomes in telomeric position.…”
Section: Discussionmentioning
confidence: 99%
“…The number and chromosomal distribution of NOR sites have been traditionally regarded as of taxonomical relevance and used many times for taxonomical inferences [see Odierna et al, 1987;Olmo et al, 1990 and references therein;Caputo et al, 2009;Trifonov et al, 2015]. Silver staining revealed a single NOR site, located on a medium-small [MS sensu Olmo et al, 1990] pair of chromosomes in telomeric position.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was proposed that the 102-chromosomal genome of the South American red vizcacha rat ( Tympanoctomys barrerae ) resulted from tetraploidization [ 42 ], subsequent chromosome painting data clearly demonstrated that all chromosomal segments are present in diploid state [ 43 ]. On the other hand, chromosome painting turned out to be very useful in confirmation of triploidy in some lizards [ 44 ]. As most fish genomes have not been involved yet in chromosome painting experiments, future molecular cytogenetic works may shed light onto the level of ploidy in their genomes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, chromosome-specific DNA was used to produce paints which were employed for cross-species chromosome painting experiments in several species of reptiles [Kasai et al, 2012b;Johnson Pokorná et al, 2015;Trifonov et al, 2015]. Additionally, chicken painting probes hybridized to reptile chromosomes revealed a strong conservation of avian sex chromosomes and autosomes in a number of squamates [Pokorná et al, 2011[Pokorná et al, , 2012.…”
mentioning
confidence: 99%